Dehydration of glycerol over H6P2W18O62/γ-Al2O3 prepared by the supercritical method. (19th December 2022) - Cui, Mingyu; Mi, Miao; Zhang, Yidong; Xu, Wei; Wang, Min; Shao, Rong; Ding, Jianfei
Abstract : H6 P2 W18 O62 /γ-Al2 O3 prepared by supercritical impregnation exhibited excellent catalytic performance. Abstract : H6 P2 W18 O62 /γ-Al2 O3 catalysts were prepared with different methods: (a) supercritical impregnation; (b) conventional wet impregnation. The obtained catalysts were characterized with XRD, SEM, N2 adsorption, NH3 -TPD, Pyridine-IR, TG, ICP, and CHNS analyses. The results showed that supercritical CO2 was helpful in enhancing the dispersity of H6 P2 W18 O62 supported on γ-Al2 O3 and increased the surface area, pore volume and size, the total acid amount, and the proportion of Brønsted acid, and the formation of coke and the leaching of H6 P2 W18 O62 were retarded. The main reason is because supercritical carbon dioxide has high solubility and diffusivity, which favors H6 P2 W18 O62 dispersion and strengthens the interaction between H6 P2 W18 O62 and hydroxyl on γ-Al2 O3 . The performances of two catalysts in glycerol dehydration were evaluated. The conversion of glycerol, selectivity and yield of acrolein, and catalytic stability were significantly enhanced on the H6 P2 W18 O62 /γ-Al2 O3 catalyst prepared by supercritical impregnation because greater total acidity is conducive for improving the conversion of glycerol, while a higher ratio of Brønsted acid sites to total acidity is conducive for enhancing the acrolein selectivity.